An Interface Theory for Input/Output Automata - Larsen, Kim G.; Nyman, Ulrik; Wasowski, Andrzej (BRICS Report Series, 2006)
Building on the theory of interface automata by de Alfaro and Henzinger we design an interface language for Lynch’s Input/Output Automata, a popular formalism used in the development of distributed asynchronous systems, not addressed by previous interface research. We introduce an explicit separation of assumptions from guarantees not yet seen in other behavioral interface theories. Moreover we derive the composition operator systematically and formally, guaranteeing that the resulting compositions are always the weakest in the sense of assumptions, and the strongest in the sense of guarantees. We also present a method for solving systems of relativized behavioral inequalities as used in our setup and draw a formal correspondence between our work and interface automata. Proofs are provided in an appendix.